2022
DOI: 10.3390/biomedicines10102332
|View full text |Cite
|
Sign up to set email alerts
|

Resistin Modulates the Functional Activity of Colostral Macrophages from Mothers with Obesity and Diabetes

Abstract: Background: Obesity and diabetes are major public health problems. Resistin is an adipokine that links the two diseases. There are few reports regarding colostrum cells and resistin from mothers with obesity and diabetes. Thus, this study aimed to determine the functional activity of macrophages present in the breast milk and colostrum of diabetic mothers with obesity and the effects of resistin on these cells. Methods: The women were divided according to BMI and glycemic status into normal weight non-diabetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 46 publications
0
2
2
Order By: Relevance
“…We found no significant differences in colostrum resistin level in relation to maternal hyperglycemic state (GDM-G1: 13.33 ng/mL, GDM-G2: 12.81 ng/mL, non-GDM: 7.89 ng/mL). However, these milk resistin values are higher than those reported by Ilcol and coworkers [101] and lower than data presented by Dalcin and coworkers [57]. In fact, we observed a higher, but not significantly, resistin level in relation to maternal hyperglycemia, while Dalcin and coworkers [57] noted the presence of significantly higher values for obese non-diabetes, normal weight diabetes, and obese diabetes groups in relation to the normal weight cohort.…”
Section: Discussioncontrasting
confidence: 80%
See 3 more Smart Citations
“…We found no significant differences in colostrum resistin level in relation to maternal hyperglycemic state (GDM-G1: 13.33 ng/mL, GDM-G2: 12.81 ng/mL, non-GDM: 7.89 ng/mL). However, these milk resistin values are higher than those reported by Ilcol and coworkers [101] and lower than data presented by Dalcin and coworkers [57]. In fact, we observed a higher, but not significantly, resistin level in relation to maternal hyperglycemia, while Dalcin and coworkers [57] noted the presence of significantly higher values for obese non-diabetes, normal weight diabetes, and obese diabetes groups in relation to the normal weight cohort.…”
Section: Discussioncontrasting
confidence: 80%
“…However, these milk resistin values are higher than those reported by Ilcol and coworkers [101] and lower than data presented by Dalcin and coworkers [57]. In fact, we observed a higher, but not significantly, resistin level in relation to maternal hyperglycemia, while Dalcin and coworkers [57] noted the presence of significantly higher values for obese non-diabetes, normal weight diabetes, and obese diabetes groups in relation to the normal weight cohort. The data for resistin concentration in different stages of lactation (first and third months) reported previously [102,103] are lower than data obtained by us; this is in line with observations that resistin level decreases with progress of lactation and might be caused by the loss of fat stores in breastfeeding mothers [101,103].…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…In the present study, all participants were tested around the 3rd to 7th day of infection, an adequate interval for RT-PCR according to local protocols [72], suggesting that cytokines can be important in the initial disease. Several studies have reported correlations between cytokines, hormones, and chronic degenerative diseases, including obesity and diabetes [66,[73][74][75].…”
Section: Discussionmentioning
confidence: 99%